Нормативно-правове регулювання фінансової безпеки держави та механізм її забезпечення в Україні - Крутько, М. А.; Krutko, M. A. (ВД "Гельветика", 2021)
У статті визначено, що з моменту прийняття Декларації про незалежність Україна становилась як цілісна й незалежна держава, захист національних інтересів якої виступає пріоритетним завданням. У такому контексті встановлено значущість питань національ- ної безпеки, та економічної безпеки держави зокрема. Проведено дослідження питання нормативно-правового забезпечення фінансової безпеки, яке є актуальним, адже Україна, як і кожна держава, прагне до економічної стабільності й фінансової самостійності, що є важливим аспектом у розрізі трансформаційних і глобалізаційних викликів сьогодення. Доведено, що фінансово-економічна безпека держави напряму залежить від взаємо- узгодженої та налагодженої стабільно-працюючої фінансової системи. В умовах внутріш- ньої та зовнішньої економічної кризи існують фактори ризику, що слугують каталізатором негативних процесів у системі фінансової безпеки держави, задля боротьби з якими необ- хідно розробити дієвий механізм забезпечення порядку. Запропоновано найдієвіші заходи забезпечення фінансової безпеки України, якими виступають: 1) насамперед удосконалення нормативно-правової бази регулювання фінансової без- пеки країни шляхом прийняття спеціалізованого закону «Про основи фінансової безпеки України», разом з яким прийняти Концепцію та Стратегію фінансової безпеки держави, де визначити засади державної політики забезпечення фінансової складової частини націо- нальної економічної безпеки; 2) обов’язкове створення ефективного органу й системи заходів, спрямованих на бо- ротьбу з корупційною складовою частиною; 3) забезпечення залучення іноземних інвестицій шляхом створення сприятливого інвестиційного клімату; 4) переймання іноземного досвіду забезпечення фінансової безпеки й імплементування міжнародних стандартів у національне законодавство; 5) створення умов для виходу коштів із тіньової економіки; 6) удосконалення регулювання кредитно-банківської системи. Визначено, що під час розробки зазначених регуляторно-забезпечуючих нормативних документів необхідно насамперед вивчити й запозичити досвід зарубіжних країн із вищим рівнем економічного й правового розвитку, імплементувати міжнародні стандарти у сфері забезпечення фінансової безпеки держави, а також приєднатися до міжнародних конвенцій досліджуваного напряму.

The article states that since the adoption of the Declaration of Independence, Ukraine has become an integral and independent state, the protection of national interests of which is a priority. In this context, the importance of issues of national security and economic security of the state in particular. A study of the issue of regulatory and legal support of financial security, which is relevant, because Ukraine, like any country seeks economic stability and financial independence, which is an important aspect in terms of transformational and globalization challenges today. It is proved that the financial and economic security of the state directly depends on a mutually agreed and well-established stable financial system. In the conditions of internal and external economic crisis there are risk factors that serve as a catalyst for negative processes in the system of financial security of the state in order to combat which it is necessary to develop an effective mechanism to ensure order. The most effective measures to ensure financial security of Ukraine are proposed, which are: 1) first of all improvement of the legal framework for regulating the financial security of the country by adopting a specialized law “On Fundamentals of Financial Security of Ukraine” to adopt the Concept and Strategy of financial security. principles of state policy to ensure the financial component of national economic security; 2) it is necessary to create an effective body and system of measures aimed at combating the corruption component; 3) ensure the attraction of foreign investment by creating a favorable investment climate; 4) adopt foreign experience in ensuring financial security and implement international standards into national legislation; 5) create conditions for the withdrawal of funds from the shadow economy; 6) improve the regulation of the credit and banking system. It is determined that in the development of these regulatory and regulatory documents it is necessary to first study and borrow the experience of foreign countries with higher economic and legal development, implement international standards in the field of financial security of the state and join international conventions.

The article states that since the adoption of the Declaration of Independence, Ukraine has become an integral and independent state, the protection of national interests of which is a priority. In this context, the importance of issues of national security and economic security of the state in particular. A study of the issue of regulatory and legal support of financial security, which is relevant, because Ukraine, like any country seeks economic stability and financial independence, which is an important aspect in terms of transformational and globalization challenges today. It is proved that the financial and economic security of the state directly depends on a mutually agreed and well-established stable financial system. In the conditions of internal and external economic crisis there are risk factors that serve as a catalyst for negative processes in the system of financial security of the state in order to combat which it is necessary to develop an effective mechanism to ensure order. The most effective measures to ensure financial security of Ukraine are proposed, which are: 1) first of all improvement of the legal framework for regulating the financial security of the country by adopting a specialized law “On Fundamentals of Financial Security of Ukraine” to adopt the Concept and Strategy of financial security. principles of state policy to ensure the financial component of national economic security; 2) it is necessary to create an effective body and system of measures aimed at combating the corruption component; 3) ensure the attraction of foreign investment by creating a favorable investment climate; 4) adopt foreign experience in ensuring financial security and implement international standards into national legislation; 5) create conditions for the withdrawal of funds from the shadow economy; 6) improve the regulation of the credit and banking system. It is determined that in the development of these regulatory and regulatory documents it is necessary to first study and borrow the experience of foreign countries with higher economic and legal development, implement international standards in the field of financial security of the state and join international conventions.
Крутько М. А. Нормативно-правове регулювання фінансової безпеки держави та механізм її забезпечення в Україні / М. А. Крутько // Наукові праці Національного університету «Одеська юридична академія». Т. 29 / голов. ред. Ю. В. Цуркан-Сайфуліна ; МОН України, НУ «ОЮА». – Одеса : Видавничий дім «Гельветика», 2021. – C. 123-128. DOI https://doi.org/10.32837/npnuola.v28i29.724
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; кредитно-банківська система; іноземні інвестиції; фінансово-економічна безпека держави; нормативно-правове забезпечення; фінансова система; credit and banking system; foreign investments; financial and economic security of the state; regulatory and legal support; financial system